Thinness and fecundability: Time to pregnancy after adolescent marriage in rural Bangladesh - Hur, Jinhee; West, Keith P.; Shamim, Abu Ahmed; Rashid, Mahbubur; Labrique, Alain B.; Wu, Lee S.F.; Ali, Hasmot; Ullah, Barkat; Schulze, Kerry J.; Klemm, Rolf D.W.; Christian, Parul (Wiley, 2022)
This article was published in Maternal Child Nutrition by Wiley [ © 2020 The Authors. Maternal & Child Nutrition published by John Wiley & Sons Ltd] and the definite version is available at: https://doi.org/10.1111/mcn.12985 The Journal's website is at: https://onlinelibrary.wiley.com/doi/full/10.1111/mcn.12985